The song of Troilus : lyric authority in the medieval book - Stillinger, Thomas C. (University of Pennsylvania Press, 1992)
The Song of Troilis traces the origins of modern authorship in the formal experimentation of medieval writers. Thomas C. Stillinger analyzes a sequence of narrative books that are in some way constructed around lyric poems: Dante's Vita Nuova, Boccaccio's Filostrato, and Chaucer's Troilus and Criseyde. The shared aim of these texts, he argues, is to imagine and achieve an unprecedented auctoritas: a "lyric authority" that combines the expressive subjectivity of courtly love poetry with the impersonal authority of Biblical commentary. Each of the three establishes its own formal and intertextual dynamics; in complex and unexpected ways, the hierarchies of Latin learning are charged with erotic force, allowing the creation of a new vernacular Book of Love. The Song of Troilus is a linked series of incisive close readings. Each chapter defines and investigates a range of philological, intertextual, and theoretical problems: in addition to explicating his three principal texts, Stillinger offers important insights into a range of medieval traditions, from Psalm commentary to Trojan historiography to Ricardian political satire. At the same time, the Song of Troilus is a sophisticated narrative of cultural change and a searching meditation on history, desire, and writing. The Song of Troilus is an original and highly readable study of three major medieval texts; it will be of compelling interest to students and scholars of medieval literature, and to all those exploring the history of authorship and the implications of literary form.
Based on the author's Ph. D. thesis, Cornell University.
Keywords: Chaucer, Geoffrey, -- -1400. -- Troilus and Criseyde.; Boccaccio, Giovanni, -- 1313-1375. -- Filostrato.; Dante Alighieri, -- 1265-1321. -- Vita nuova.; Chaucer, Geoffrey, -- approximately 1340-1400. -- Troilus and Criseyde.; Troilus and Criseyde (Chaucer, Geoffrey); Vita nuova (Dante Alighieri); Dante (Alighieri). -- Vita nuova.; Boccaccio, Giovanni. -- Filostrato.; Chaucer, Geoffrey. -- Troilus and Criseyde.; Troilus (Legendary character) in literature.; Literature, Medieval -- History and criticism.; Influence (Literary, artistic, etc.); Trojan War -- Literature and the war.; Authority in literature.; Rhetoric, Medieval.; Intertextuality.; Littérature médiévale -- Histoire et critique.; Influence littéraire, artistique, etc.; Rhétorique médiévale.; Intertextualité.; Troïlos (Personnage légendaire) dans la littérature.; Guerre de Troie dans la littérature.; Autorité dans la littérature.; POETRY -- English, Irish, Scottish, Welsh.; LITERARY CRITICISM -- Medieval.; Authority in literature; Intertextuality; Literature, Medieval; Rhetoric, Medieval; Troilus (Legendary character) in literature; Auctoritas; Criticism, interpretation, etc.